Some geometric aspects on submanifolds theory - Singh, Khushwant (My University, 2013)
In the present thesis we have studied slant and bisalant suvmanifolds of almost complex almost contact and LP-contact manifold.
PhD
Keywords: warped product; slant submanifolds